The role of union leader-member relationship capital within trade union for mental health - Koh, Jacqueline; Mohd Salleh, Lailawati; Kumar, Naresh; Mansor, Zuraina; Mohd Salleh, Noorziah; Ag Budin, Dg Kamisah; Rosline, Abdul Kadir; Parasuraman, Balakrisnan (Global Academy of Training & Research (GATR) Enterprise, 2016)
Objective – There are three main objectives of this study. First, this study is to examine the influence of union effectiveness and perceived union support on union relationship capital to achieve positive mental health in the workplace. Next, this study is to investigate the interdependency of the dimensions of union relationship capital: communication, trust and commitment between the union leader and union members in improving and strengthening the relationship within the union. Lastly, this study is to investigate the role of relationship capital as the mediator between union effectiveness, perceived union support and mental health.